S102 The effect of respiratory viruses on the lung microbiome of adults with cystic fibrosis. (14th November 2013) - Flight, WG; Marchesi, JR; Smith, A; Norville, P; Mutton, KJ; Webb, AK; Bright-Thomas, RJ; Jones, AM; Mahenthiralingam, E
Abstract : Introduction: Viral respiratory infection (VRI) has been implicated in the pathogenesis of cystic fibrosis (CF) lung disease and it has been hypothesised that respiratory viruses may predispose CF patients to acquisition of bacterial pathogens. We performed a prospective observational study to determine whether VRI leads to a change in the respiratory microbiome of adults with CF. Methods: Participants provided sequential paired sputum samples over a ten month period. One sputum sample from each visit was processed using conventional culture. The second sample was analysed with 16S rRNA gene pyrosequencing and ribosomal intergenic spacer analysis (RISA) to examine bacterial diversity. Polymerase chain reaction assays for nine respiratory viruses were also performed on the second sample. Study visits were classified as "stable, " "viral" or "non-viral exacerbation." Generalised estimating equation models were used to examine differences between these groups of study visits. Statistical analysis accounted for repeated observations from individual patients. Results: Eighteen patients provided a total of 77 paired sputum samples over a median follow-up period of 290 days (range 62–359). 23/46 (50%) study visits were positive for a respiratory virus with rhinovirus accounting for 56% of cases. 19/46 (41%) study visits met the pre-specified criteria for pulmonary exacerbation of which 11 (58%) were virus-positive and 8 (42%) were virus-negative. Conventional culture did not identify any new bacterial species during the study period. A mean of 5453 (SD 2847) reads per sample were detected by 16S rRNA gene pyrosequencing. The mean Shannon Index was 0.59 (SD 0.58) with a mean richness of 15.1 (SD 7.9) genera. No consistent change in bacterial diversity indices or relative abundance of individual genera was seen in response to either VRI or non-viral exacerbations. The majority of patients had highly variable RISA and 16S rRNA gene profiles during follow-up. A subset of four patients (22%) had a stable respiratory microbiome which was heavily dominated by Pseudomonas aeruginosa throughout despite episodes of VRI, pulmonary exacerbation and antibiotic therapy. Conclusions: Longitudinal change of the respiratory microbiome varies considerably among adults with CF. No consistent effect of either VRI or pulmonary exacerbation on the lung microbiome was observed.